Lights and Shadows of Arbitration in Government Procurement - Campos Medina, Alexander (2015)
The present event talks about some relevant aspects in arbitration on public procurement matter, such as additional the non-arbitrability of additional provisions, the use of interim measures against administrative penalties and corruption of arbitration on public procurement matter. The discussion is done in the frame of the new Public Procurement Law.